Liquid-liquid equilibrium of poly(ethylene glycol) 2000 plus potassium citrate plus water at (25, 35, and 45) degrees C - M., Jayapal; I., Regupathi; T., Murugesan (AMER CHEMICAL SOC, 1155 16TH ST, NW, WASHINGTON, DC 20036 USA, 2007)
Liquid-liquid equilibrium for an aqueous two-phase system containing poly(ethylene glycol) 2000 + potassium citrate + water was studied at three different temperatures of (25, 35, and 45) degrees C. The binodal curve was fitted to an empirical equation relating the concentrations of PEG 2000 and potassium citrate, and the coefficients were estimated for the respective temperatures. Tie line compositions were correlated using Othmer-Tobias and Bancroft equations, and the parameters are also reported.